(3GdhaG HCMhGd GdeUWais - (3GHf GdLhRj, YHO GdQMef Hf Ydj Hf eMeO,s 508-597 (3g`(B.s ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2005)
(3jJfGhd GdcJGH GdQShd Ydjg GdUdGI hGdSdGe(B.s
Keywords: (3eMeO (B((3Udi Gddg Ydjg hSde(B)(3,s -- 53 (3b(B. (3g`(B-11 (3g`(B.s; (3GdSjQI GdfHhjIs